2009
DOI: 10.1111/j.1365-2788.2009.01196.x
|View full text |Cite
|
Sign up to set email alerts
|

Autonomy in relation to health among people with intellectual disability: a literature review

Abstract: In spite of decades of promoting autonomy, the exercise of autonomy in relation to health has so far rarely been an issue in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 51 publications
0
33
0
2
Order By: Relevance
“…Since intellectual disability populations face additional barriers to PA [70,71] and have fewer choices and less control of their health than individuals who do not have intellectual disabilities [72], supporting this group to change PA behaviour may be challenging. For example, a recent weight loss study for adults with intellectual disabilities [73] found that a lack of sufficient support from carers/relatives and poor communication among carers, were identified as being barriers to change.…”
Section: Discussionmentioning
confidence: 99%
“…Since intellectual disability populations face additional barriers to PA [70,71] and have fewer choices and less control of their health than individuals who do not have intellectual disabilities [72], supporting this group to change PA behaviour may be challenging. For example, a recent weight loss study for adults with intellectual disabilities [73] found that a lack of sufficient support from carers/relatives and poor communication among carers, were identified as being barriers to change.…”
Section: Discussionmentioning
confidence: 99%
“…There are also a number of ethical challenges in this intervention because people with ID are in need of professional care, but also have the basic right to autonomy and self-determination [41]. This will be dealt with in a separate qualitative study within this project.…”
Section: Discussionmentioning
confidence: 99%
“…Normaliseringsprincipen (Nirje, 1969; är en betydande utgångspunkt för delaktighetsideologin och den moderna funktionshinderspolitiken, i både Sverige och övriga västvärlden (Kjellberg, 2002;Wullink et al, 2009). I denna princip specificeras rätten till till åldersadekvata erfarenheter i förhållande till att vara barn, ungdom, vuxen och äldre.…”
unclassified